2002
DOI: 10.1038/nature00783
|View full text |Cite
|
Sign up to set email alerts
|

New components of the spliced leader RNP required for nematode trans-splicing

Abstract: Pre-messenger-RNA maturation in nematodes and in several other lower eukaryotic phyla involves spliced leader (SL) addition trans-splicing. In this unusual RNA processing reaction, a short common 5' exon, the SL, is affixed to the 5'-most exon of multiple pre-mRNAs. The nematode SL is derived from a trans-splicing-specific approximately 100-nucleotide RNA (SL RNA) that bears striking similarities to the cis-spliceosomal U small nuclear RNAs U1, U2, U4 and U5 (refs 3, 4); for example, the SL RNA functions only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…The SL RNA is transcribed from the intragenic spacer by RNA polymerase II, resulting in a pre-RNA which contains the SL sequence at its 5′ end, and binding sites for various components of the splicing machinery in its 3′ end [9,10]. The SL sequence is then removed from the nascent SL transcript and is trans-spliced on to the 5′ end of the nascent mRNA, through a biochemical pathway that bears many similarities to the cis-splicing pathway [11], although certain proteins have been shown to be specifically required for trans-splicing [10,11] In vitro biochemical systems employing nuclear extracts have been used to extensively dissect the trans-splicing pathway in the intestinal parasite Ascaris suum [7,[10][11][12][13]. These studies have resulted in the identification of a number of factors that are involved in the trans-splicing process [9][10][11] and have also succeeded in identifying the structural factors in the SL pre-RNA that are necessary for correct processing of the nascent transcript [7].…”
Section: Introductionmentioning
confidence: 99%
“…The SL RNA is transcribed from the intragenic spacer by RNA polymerase II, resulting in a pre-RNA which contains the SL sequence at its 5′ end, and binding sites for various components of the splicing machinery in its 3′ end [9,10]. The SL sequence is then removed from the nascent SL transcript and is trans-spliced on to the 5′ end of the nascent mRNA, through a biochemical pathway that bears many similarities to the cis-splicing pathway [11], although certain proteins have been shown to be specifically required for trans-splicing [10,11] In vitro biochemical systems employing nuclear extracts have been used to extensively dissect the trans-splicing pathway in the intestinal parasite Ascaris suum [7,[10][11][12][13]. These studies have resulted in the identification of a number of factors that are involved in the trans-splicing process [9][10][11] and have also succeeded in identifying the structural factors in the SL pre-RNA that are necessary for correct processing of the nascent transcript [7].…”
Section: Introductionmentioning
confidence: 99%
“…SL RNAs are bound to the Sm proteins that are also core proteins in spliceosomal U1, U2, U4, and U5 snRNPs (Bruzik et al 1988; Thomas et al 1988;Van Doren and Hirsh 1988). In addition to the Sm proteins, the SL snRNP from Ascaris, a nematode that is distantly related to C. elegans, contains two novel proteins of 95 kDa (SL95p) and 30 kDa (SL30p) (Denker et al 1996(Denker et al , 2002. SL30p interacts with the splicing protein SF1/BBP that binds to the branchpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the sequence looks like the AU-rich motif bound by AREbinding proteins. However, to date, no SL2-specific proteins have been identified, and the homologs of the transsplicing-specific proteins identified in Ascaris (Denker et al 2002) have been found on SL1 but not SL2 in C. elegans (MacMorris et al 2007). Finally, many mutations that fortuitously reduced the proposed base-pairing interfered with SL2 trans-splicing (Huang et al 2001).…”
Section: The Uayyuu Motif Of the Ur Elementmentioning
confidence: 99%